Perfecting the Advanced 2D Multi-electrode Electrical Exploration Method - Duc Minh, Vu; Anh Chung, Do (VNU Journal of Science: Mathematics - Physics, 2018)
The Advanced Multi-electrode Electrical Sounding method (AMES) proposed by us was introduced at VNU. Journal of Mathematics-Physics, No. 31 (3), 2015. However, the published results are mostly focused on the symmetric MC array and tested on a theoretical model. In this paper, the authors continue systematically presenting and supplementing the results obtained after the study, namely the finalization and renaming of the AMES method into the Advanced 2D Multi-electrode Electrical Exploration (AMEE) method, including MC array, data collecting and processing, and testing on theoretical model and practical application  to confirm the superiority of this method.